AN ANALYTICAL COMPREHENSIVE REVIEW PAPER ON HARNESSING THE POWER OF HERBAL DRUGS IN PHARMACY: FROM ANCIENT ROOTS TO MODERN THERAPEUTICS - , Sakshi Sharma; Manan Agrawal; Sapna Vyas; Mangal S Panwar (Journal of Global Pharma Technology, 2025)
Herbal medicines have been central in the establishment and development of pharmacy as one of the oldest and most reliable sources of therapeutic drugs. With their rich biodiversity and wide reservoir of bioactive metabolites, medicinal plants continue to yield new leads for drug discovery and development. In contemporary pharmacy, herbal drugs not only find extensive use as first-line therapies in numerous cultures but also used as complementary medicines in combination with standard drugs. Their array of pharmacological activities—such as anti-inflammatory, antioxidant, antimicrobial, and anticancer properties-emphasizes their therapeutic value. In addition, the herbal drugs have benefits like reduced toxicity, cost-effectiveness, and patient compliance. Still, issues pertaining to standardization, quality control, safety, and scientific proof remain essential areas of attention. The coordination of traditional knowledge and contemporary pharmaceutical research is the key to maintaining the effectiveness, safety, and international acceptability of medicinal plants. Accordingly, herbal medicines remain of extremely important significance in pharmacy, serving to bridge the gap between traditional healing systems and evidence-based practice. Keywords: Herbal drugs, Modern therapeutics, Pharmacy.